Class Management in Improving Student Learning Participation in Elementary School Madrasah in Indonesia - Ach. Baidowi; Himad Ali; Sari Nusantara Putri (Al Irsyad, 2024)
Good classroom management is influenced by effective leadership, harmonious relationships, and continuously improving facilities. Despite some shortcomings in facilities, student awareness, and the application of learning methods, this study aims to explore classroom management from planning to supervision in order to enhance student learning participation. The research method used is qualitative through a literature review by collecting data from scholarly articles on Google, focusing on classroom management in Madrasah Ibtidaiyah, through a series of analyses and conclusions. The research findings show that classroom management strategies in Madrasah Ibtidaiyah aim to create a conducive and effective learning environment. This includes lesson planning, classroom arrangement, student motivation, and attention to students' physical and psychological conditions. Teachers need to manage student activities and behavior with care and reinforcement, as well as use appropriate methods. Humanistic and democratic classroom management supports effective interaction, productive relationships, and optimal student development. Classroom organization begins with thorough learning preparation, such as developing lesson plans, selecting media, assigning group tasks, and consistent, clear classroom rules.